Organizational Learning: Mechanisms, Culture, and Feasibility - Popper, Micha; Lipshitz, Raanan (Management learning, 2000)
The burgeoning literature on organizational learning attests to the considerable interest engendered by `organizational learning' and `learning organizations'. At the same time it indicates considerable confusion surrounding these subjects. We discuss four controversial issues regarding organizational learning: (1) What are the similarities and differences between individual and organizational learning? (2) What are the conditions that promote productive organizational learning? (3) When is organizational learning feasible? (4) How is organizational learning related to learning organizations? We suggest that (1) although individual and organizational learning involve information processing, they require different mechanisms to convert information to actionable knowledge at different (individual vs organizational) systemic levels; (2) productive organizational learning requires a learning culture that consists of commitment to learning, valid knowledge, transparency, issue orientation and accountability; (3) the feasibility of organizational learning is enhanced by high environmental uncertainty, high costs of potential error, high level of members' professionalism, and a strong leadership commitment to learning, (4) learning organizations are organizations that embed institutionalized learning mechanisms within a learning culture.